2023
DOI: 10.1007/s11301-023-00318-8
|View full text |Cite|
|
Sign up to set email alerts
|

Beyond conventional corporate responses to climate change towards deep decarbonization: a systematic literature review

Abstract: Over the past 20 years, the literature on corporate responses to climate change has offered a vast array of theoretical and practical insights into organizational efforts to reduce business-related carbon emissions. However, it remains unclear whether these efforts will result in significant reductions of carbon emissions. Presently, it becomes crucial to understand, if, why, and how companies can effectively respond to the current challenges of deep decarbonization, defined as the process of emission reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 108 publications
(207 reference statements)
0
6
0
Order By: Relevance
“…Second, we build on the literature on corporate sustainability, which has investigated ambidextrous behaviour in the context of green or sustainable innovations in organisations, e.g., [19,20]. We contribute to this literature by looking, more specifically, at the connection between ambidexterity and corporate decarbonisation efforts [4].…”
Section: Knowledge Gaps and Contributionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, we build on the literature on corporate sustainability, which has investigated ambidextrous behaviour in the context of green or sustainable innovations in organisations, e.g., [19,20]. We contribute to this literature by looking, more specifically, at the connection between ambidexterity and corporate decarbonisation efforts [4].…”
Section: Knowledge Gaps and Contributionsmentioning
confidence: 99%
“…In response to pressures from governments, investors, and other stakeholders, many companies have been taking action to reduce their emissions and adopting a variety of carbon and energy management practices [21]. The literature on climate action from an organisational perspective has investigated issues such as the drivers of corporate climate action, e.g., [7,22], barriers from external, internal, and dimensional perspectives [4], and actions that organisations can take [4,7,8,11]. We turn our attention to the existing body of literature looking at the actions that can be employed by companies in response to climate risks, as this stream of research has been mostly descriptive of 'what' they do, lacking insights on 'how' organisations adopt the proposed strategies and practices.…”
Section: Background 21 Corporate Action For Climate Changementioning
confidence: 99%
See 2 more Smart Citations
“…We found that as corporate climate targets become more ambitious, the presence of key explanatory factors -such as leadership engagement, continual management support, employee involvement, participation in climate initiatives, and stakeholder collaboration -also increases. Corporate responses to climate change encompass the drivers, the mitigating strategies and actions, and the facilitating criteria to overcome these barriers (Johnson et al 2023). When considering implementable strategies and actions, Lee (2012) provides a comprehensive overview of carbon management activities in six categories.…”
Section: Introductionmentioning
confidence: 99%